Begräbnis der Revolutionsopfer. "Die Kranzdeputationen der Matrosen im Zuge am Brandenburger Tor". Aus: Album XI
Begräbnis der Revolutionsopfer. "Die Kranzdeputationen der Matrosen im Zuge am Brandenburger Tor". Aus: Album XI.